Studies on the Endocrine and Neuroendocrine Control of Broodiness in the Yuehuang Hen - Kagya-Agyemang, J.K.; Shendan, S.; Yinzuo, B. (International Journal of Poultry Science, 2012)
The hypothesis that serotonin (5-HT) and dopamine stimulate prolactin (PRL) release, either directly from the pituitary gland or by acting through Vasoactive Intestinal Peptide (VIP), was investigated by assessing the role of hypothalamic dopamine and 5-HT in the control of broodiness and PRL release in Cantonese native chicken breed called the Yuehuang hen. A second objective was to assess the involvement of hypothalamic VIP in the control of broodiness and PRL release by using dopamine and serotonin receptor antagonists respectively. In Experiment 1, two hundred laying hens from battery cages were transferred to floor pens with nest boxes to induce broodiness. Starting from the second day after the onset of broodiness, sixty hens were allotted into groups 1, 2 and 3 respectively, corresponding to chlorpromazine-treated (n = 20), cyproheptadine-treated (n = 20) and control (n = 20) groups. Blood samples were collected from the wing veins of hens in each group on days 2, 5, 9, 14 and 19 respectively after the onset of broodiness for radioimmunoassay of PRL and Luteinizing Hormone (LH). Results indicate that in the drug treated hens which terminated broodiness, the concentration of plasma PRL decreased significantly (p